Empowering Msmes for the Digital Era: A Comprehensive SWOT and AHP – Based Development Strategy in Bekasi Regency - Fauzi, Firman; Siregar, Hermanto; Barus, Baba; Syahbana, Galuh (International Journal of Integrative Sciences, 2025)
Bekasi Regency, known as an industrial hub in Indonesia, has witnessed a surge in digital transformation efforts among Micro, Small, and Medium Enterprises (MSMEs). Despite their significant economic contributions, MSMEs face challenges such as uneven digital infrastructure, limited digital literacy, and organizational readiness gaps. This study investigates strategies for empowering MSMEs to embrace digital transformation using a hybrid SWOT and Analytic Hierarchy Process (AHP) methodology. SWOT analysis explores the internal and external factors influencing MSME readiness, while AHP prioritizes strategic alternatives for actionable recommendations.The findings highlight critical factors, including the need for enhanced digital infrastructure, increased digital literacy among MSME stakeholders, and strengthened cross-sectoral collaborations to address challenges such as limited resources and cybersecurity concerns. The integration of SWOT and AHP methodologies results in prioritized strategies, with the expansion of digital infrastructure emerging as the top priority, followed by fostering digital partnerships and enhancing digital literacy.Managerial implications emphasize the importance of equitable digital access, the creation of MSME digitalization centers, and the development of curated e-commerce platforms to strengthen competitiveness. These strategies are essential to promoting sustainable and inclusive growth in the region. The study concludes that government and private-sector collaboration is vital for bridging digital divides and enabling MSMEs to thrive in an increasingly digital economy.This research contributes to the limited discourse on MSME digital transformation in emerging markets, providing a strategic framework to achieve inclusive growth and regional economic resilience. Future research should explore the longitudinal impact of these strategies on MSME development and their scalability across diverse socio-economic contexts